Morphological and molecular evidence supports specific recognition of the recently extinct Bettongia anhydra (Marsupialia: Macropodidae) - McDowell, M.; Haouchar, D.; Aplin, K.; Bunce, Michael; Baynes, A.; Prideaux, G. (American Society of Mammalogists, 2015)
In 1933, geologist and explorer Michael Terry collected the skull of a small macropodid captured by members of his party near Lake Mackay, western Northern Territory. In 1957, this skull was described as the sole exemplar of a distinct subspecies, Bettongia penicillata anhydra, but was later synonymized with B. lesueur and thereafter all but forgotten. We use a combination of craniodental morphology and ancient mitochondrial DNA to confirm that the Lake Mackay specimen is taxonomically distinct from all other species of Bettongia and recognize an additional specimen from a Western Australian Holocene fossil accumulation. B. anhydra is morphologically and genetically most similar to B. lesueur but differs in premolar shape, rostrum length, dentary proportions, and molar size gradient. In addition, it has a substantial mitochondrial cytochrome b pairwise distance of 9.6–12% relative to all other bettongs. The elevation of this recently extinct bettong to species status indicates that Australia’s mammal extinction record over the past 2 centuries is even worse than currently accepted. Like other bettongs, B. anhydra probably excavated much of its food and may have performed valuable ecological services that improved soil structure and water infiltration and retention, as well as playing an important role in the dispersal of seeds and mycorrhizal fungal spores. All extant species of Bettongia have experienced extensive range contractions since European colonization and some now persist only on island refugia. The near total loss of these ecosystem engineers from the Australian landscape has far-reaching ecological implications.